The little elongation complex regulates small nuclear RNA transcription. - Smith, E.R.; Lin, C.; Garrett, A.S.; Thornton, J.; Mohaghegh, N.; Hu, D.; Jackson, J.; Saraf, A.; Swanson, S.K.; Seidel, C.; Florens, L.; Washburn, M.P.; et al. (Molecular Cell, 2011)
Eleven-nineteen lysine-rich leukemia (ELL) participates in the super elongation complex (SEC) with the RNA polymerase II (Pol II) CTD kinase P-TEFb. SEC is a key regulator in the expression of HOX genes in mixed lineage leukemia (MLL)-based hematological malignancies, in the control of induced gene expression early in development, and in immediate early gene transcription. Here, we identify an SEC-like complex in Drosophila, as well as a distinct ELL-containing complex that lacks P-TEFb and other components of SEC named the "little elongation complex" (LEC). LEC subunits are highly enriched at RNA Pol II-transcribed small nuclear RNA (snRNA) genes, and the loss of LEC results in decreased snRNA expression in both flies and mammals. The specialization of the SEC and LEC complexes for mRNA and snRNA-containing genes, respectively, suggests the presence of specific classes of elongation factors for each class of genes transcribed by RNA polymerase II.